Freedom to Learn-Independent Campus: EFL Preservice Teachers’ Voice on Their Pedagogical Competence - Mardhatillah Mardhatillah (STAI Hubbulwathan Duri, 2023)
The primary objective of the current study is to analyze the perspectives held by preservice EFL teachers regarding the level of pedagogical competence they possess. The current study tries to fill the gap of previous studies since there is no study concerned with EFL preservice teachers’ pedagogical competence completely in their study. And may improve teacher preparation programs both directly and indirectly. Thus, a questionnaire based on a Likert scale was utilized in order to obtain the required data. The data were obtained from one of the universities in East Sumatra, a total of 31 preservice teachers in English education programs in the university were given the questionnaire and their responses were collected. The findings of the study revealed favorable opinions regarding the level of pedagogical competence exhibited by participants in the teaching assistantship program. In general, a significant proportion of the findings indicated that they had implemented pedagogical competence during the program. With minor obstacles when implementing it.